Evaluation of automated molecular tests for the detection of SARS‐CoV‐2 in pooled nasopharyngeal and saliva specimens. Issue 8 (16th June 2021) - Al‐Hail, Hamad; Mirza, Faheem; Al Hashemi, Alaa; Ahmad, Muneera Naseer; Iqbal, Muhammad; Tang, Patrick; Hasan, Mohammad Rubayet
Abstract: Background: Pooling of samples for SARS‐CoV‐2 testing in low‐prevalence settings has been used as an effective strategy to expand testing capacity and mitigate challenges with the shortage of supplies. We evaluated two automated molecular test systems for the detection of SARS‐CoV‐2 RNA in pooled specimens. Methods: Pooled nasopharyngeal and saliva specimens were tested by Qiagen QIAstat‐Dx Respiratory SARS‐CoV‐2 Panel (QIAstat) or Cepheid Xpert Xpress SARS‐CoV‐2 (Xpert), and the results were compared to that of standard RT‐qPCR tests without pooling. Results: In nasopharyngeal specimens, the sensitivity/specificity of the pool testing approach, with 5 and 10 specimens per pool, were 77%/100% ( n  = 105) and 74.1%/100% ( n  = 260) by QIAstat, and 97.1%/100% ( n  = 250) and 100%/99.5% ( n  = 200) by Xpert, respectively. Pool testing of saliva (10 specimens per pool; n  = 150) by Xpert resulted in 87.5% sensitivity and 99.3% specificity compared to individual tests. Pool size of 5 or 10 specimens did not significantly affect the difference of RT‐qPCR cycle threshold (CT ) from standard testing. RT‐qPCR CT values obtained with pool testing by both QIAstat and Xpert were positively correlated with that of individual testing (Pearson's correlation coefficient r  = 0.85 to 0.99, p  < 0.05). However, the CT values from Xpert were significantly stronger ( p  < 0.01, paired t test) than that of QIAstat in a subset of SARS‐CoV‐2 positive specimens, with mean differences of −4.3 ± 2.43 and −4.6 ± 2 for individual and pooled tests, respectively. Conclusion: Our results suggest that Xpert SARS‐CoV‐2 can be utilized for pooled sample testing for COVID‐19 screening in low‐prevalence settings providing significant cost savings and improving throughput without affecting test quality. Abstract : Pooled sample testing for SARS‐CoV‐2 using Cepheid Xpert and Qiagen QIAstat tests was evaluated. Analytical sensitivity of Xpert for detection of SARS‐CoV‐2 is higher than QIAstat. Sensitivity and specificity of detection in pool of 10 NP swabs by Xpert are 100% and 99.5% and by QIAstat are 74.1% and 99.5%, respectively. Sensitivity and specificity of detection in pool of 10 saliva samples by Xpert are 87.5% and 99.3%, respectively.